PENGEMBANGAN BAHAN AJAR TEMATIK INTEGRATIF BERBASIS LINGKUNGAN KELAS V DI MADRASAH IBTIDAIYAH NURUL HAROMAIN KULONPROGO YOGYAKARTA - Norma Yunaini (Pedagogia: Jurnal Ilmiah Pendidikan Dasar Indonesia, 2019)
This research departs from the problem of the still low quality of the thematic learning process in the classroom, and the teacher's ability to develop teaching materials. The main objective of this study was to produce an environment-based thematic learning design in MI Nurul Haromain Kulon Progo Yogyakarta class V in fostering student creativity. This study uses a research and development method or "Research and Development" (R&D) with the following steps: 1) conducting preliminary research, 2) planning, 3) developing a prototype of the learning model including: mapping IC and BC with selected themes, theme map, 4) tests to the research subjects were taken as many as twenty-two students. The school chosen is MI which is conducive to environment-based thematic learning. Data analysis techniques using descriptive qualitative analysis techniques. This research resulted in the development of teaching materials that are packaged by utilizing the environment as a medium and learning resource. The results of the application of teaching materials, students are more enthusiastic in the learning process, because in the learning process students not only get an understanding of the lesson, but also an attitude of responsibility and care for the environment. The implementation of this learning plan includes four cognitive, affective, spiritual and psychomotor domains, so that it is appropriate for the teacher to use in the learning process.